Do institutions matter for entrepreneurial development? - Ruta Aidis (IZA World of Labor, 2017)
Supportive institutional environments help build the foundations for innovative and productive entrepreneurship. A few post-Soviet countries have benefitted from international integration through EU membership, which enabled the development of democracy and free market principles. However, many post-Soviet economies continue to face high levels of corruption, complex business regulations, weak rule of law and uncertain property rights. For them, international integration can provide the needed support to push through unpopular yet necessary stages of the reform process.
Keywords: P2; D02; P5; 330; entrepreneurship; institutions; transition countries